3D Printable Ca(OH)2-based geopolymer concrete with steel fiber reinforcement - Youssef Mortada (16810656) (2025)
This study investigates the impact of varying steel fiber (SF) content (0%, 0.8%, 1.0%, and 1.2% by volume) on the mechanical and durability properties of 3D-printed Ca(OH)2-activated geopolymer concrete (GPC). The addition of 1.2% SF improved flexural strength by 69% at 7 days and 16% at 28 days, while tensile strength more than doubled to 3.75 MPa at 28 days. Although compressive strength remained unaffected at 43 MPa, SF enhanced interlayer bond strength by 20%, which is crucial for layer cohesion in 3D-printed structures. Additionally, the elastic modulus increased by 7%, contributing to improved stiffness. Durability assessments, including autogenous shrinkage and self-induced stress, indicated a slight reduction in shrinkage of SF-reinforced samples, with no significant effect on self-induced stress. Microstructural analysis using scanning electron microscopy (SEM) and X-ray micro-computed tomography (µCT) demonstrated the crack-bridging behavior of steel fibers, enhancing ductility and fracture resistance. There was a slight increase in porosity (5.34%) of SF-reinforced samples without negatively affecting their mechanical properties. Notably, SF improved early-age toughness and controlled crack propagation across printed layers, addressing a critical challenge in 3D-printed concrete. The novelty of this work lies in successfully reinforcing 3D-printed Ca(OH)2-activated GPC with recycled steel fibers, enhancing mechanical properties, interlayer bonding, and durability without compromising printability. This study offers a sustainable reinforcement strategy for 3D printing in construction. Other Information Published in: Materials and Structures License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1617/s11527-025-02600-5